2015
DOI: 10.1007/s00253-015-7235-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fermentation conditions on polysaccharide production and the activities of enzymes involved in the polysaccharide synthesis of Cordyceps militaris

Abstract: The influence of different fermentation conditions on intracellular polysaccharide (IPS) production and activities of the phosphoglucomutase (PGM), UDPG-pyrophosphorylase (UGP), phosphoglucose isomerase (PGI), UDPG-dehydrogenase (UGD), and glucokinase (GK) implicated in metabolite synthesis in Cordyceps militaris was evaluated. The highest IPS production (327.57 ± 6.27 mg/100 mL) was obtained when the strain was grown in the optimal medium containing glucose (40 g · L(-1)), beef extract (10 g · L(-1)), and CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…In this study, Ca 2+ addition enhanced PGI and PGM enzyme activity, whereas Na + increased UGP activity. The results from (Zhu et al 2016) showed that higher activities of PGM, UGP, and PGI were desirable for the rate of IPS biosynthesis in C. militaris. The activities of a-PGM and UDPase were highly correlated with the amount of polysaccharide produced in S. thermophilus and A. pullulans (Degeest and De Vuyst 2000;Pan et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this study, Ca 2+ addition enhanced PGI and PGM enzyme activity, whereas Na + increased UGP activity. The results from (Zhu et al 2016) showed that higher activities of PGM, UGP, and PGI were desirable for the rate of IPS biosynthesis in C. militaris. The activities of a-PGM and UDPase were highly correlated with the amount of polysaccharide produced in S. thermophilus and A. pullulans (Degeest and De Vuyst 2000;Pan et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…These three enzymes play key roles in pathways of metabolite synthesis. Higher activities of PGM, UGP, and PGI were desirable for the biosynthetic rate of IPS in Cordyceps militaris (C. militaris), which is a member of Ascomycota (Zhu et al 2016). The activities of PGM and UGP highly correlated with the amount of polysaccharide produced in Streptococcus thermophilus (S. thermophilus) and Aureobasidium pullulans (A. pullulans) (Degeest and De Vuyst 2000;Pan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cordyceps militaris (CM), a traditonal Chinese edible and medicinal mushroom, usually called Bei Dong Chong Xia Cao and Yong Chong Cao, belonging to the phylum of Ascomycota and class of Pyrenomycetes, has been proved having similar pharmacological effect to Cordyceps sinensis (Yue, Ye, Zhou, Sun, & Lin, ; Zhu et al, ). CM has been used as a medicine for over hundreds years in many Asian countries especially in China for containing abundant special natural components with biological and pharmacological activities, such as cordycepin (3′‐deoxyadenosine), adenosine, cordycepic acid, SOD enzyme, and cordyceps polysaccharides (CP) (Cui, ).…”
Section: Introductionmentioning
confidence: 99%
“…17,[20][21][22][23][24][25] Most of cyanobacteria have efficient carbon concentration mechanisms (CCM) which could transport and accumulate inorganic carbon actively (Ci; HCO 3 glucose pyrophosphorylase and UDP-glucose dehydrogenase, were relatively conserved, which played important roles in EPS production. [32][33][34][35][36][37][38][39][40][41] Based on previous reports, [42][43][44] and KEGG pathway, a simplied biosynthesis pathway for biosynthesis of cyanobacterial EPS was summarized ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%